2002
DOI: 10.1115/1.1432665
|View full text |Cite
|
Sign up to set email alerts
|

Applied Tribology: Bearing Design and Lubrication

Abstract: The primary focus of this book is the application of tribology to the design and analysis of bearings and related mechanical components. In order to make the book more useful to a wide audience, the authors attempted to maintain a balance between theory and practical application. In the view of this reviewer, they were quite successful in meeting that goal.The orientation of the book is clear from the amount of space and coverage allocated to different topics in tribology. The first part of the book, which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 0 publications
0
49
0
Order By: Relevance
“…Only few information can be found in general books on Tribology and Lubrication. In their book [2], Khonsari and Booser have indicated that the oil hydraulic lifts are also used during the very low rotational speed operation, i.e. turning speed operation (several revolutions per minute), in order to reduce the friction torque and the wear of the hydrodynamic bearings.…”
mentioning
confidence: 99%
“…Only few information can be found in general books on Tribology and Lubrication. In their book [2], Khonsari and Booser have indicated that the oil hydraulic lifts are also used during the very low rotational speed operation, i.e. turning speed operation (several revolutions per minute), in order to reduce the friction torque and the wear of the hydrodynamic bearings.…”
mentioning
confidence: 99%
“…These attributes are generally larger in scale than the surface finish of a typical bearing or gear (typically from 0.025-0.3 m in arithmetic roughness [1]), but in special cases they can be only a few nm in size. Several attributes of textured surfaces are depicted in Figure 1.…”
Section: Attributes Of Textured Surfacesmentioning
confidence: 99%
“…The Wendt (Wendt, 1933) and the surface drag losses (Khonsari & Booser, 2008) empirical formulas have been used to assess the friction factor λ for journal and thrust bearings, respectively.…”
Section: Fem Groove Mixing Theorymentioning
confidence: 99%